2017
DOI: 10.18805/lr.v0i0.8398
|View full text |Cite
|
Sign up to set email alerts
|

Influence of integrated nutrient management on growth, yield parameters and yield in French bean (Phaseolus vulgaris L.)

Abstract: An investigation was carried out during rabi season of 2013-14 at vegetable farm, College of Horticulture, Mandsaur (Gwalior) to study the effect of integrated nutrient management on growth, yield parameters and yield in French bean. The treatments comprised six nutrient levels N 1 , N 2 , N 3 , N 4 , N 5 and N 6 and three varieties viz., Arka Komal (V 1 ), Contender (V 2 ) and Swarna Priya (V 3 ). It was noticed that application of nutrient levels and varieties had significant influence on growth, yield and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
5
5
0
Order By: Relevance
“…A significant increase in the number of seeds/pods probably may be due to balanced nutrition and proper vegetative growth which later converted into reproductive phase and resulted might in a greater number of seeds. The results were similar to [13].…”
Section: Yield Attributes and Yieldsupporting
confidence: 83%
See 1 more Smart Citation
“…A significant increase in the number of seeds/pods probably may be due to balanced nutrition and proper vegetative growth which later converted into reproductive phase and resulted might in a greater number of seeds. The results were similar to [13].…”
Section: Yield Attributes and Yieldsupporting
confidence: 83%
“…Rhizobium and phosphate solubilizing bacteria (PSB) assume countless importance on account of their dynamic role in N 2 -fixation and P solubilizations. Rhizobium and PSB use have been beneficial for increasing French bean productivity" [13].…”
Section: Introductionmentioning
confidence: 99%
“…The increased growth with substitution of N by organic manures might be due to the fact that organic manures release nutrients slowly (Sharma et al, 2015), resulting in enhanced nutrient use efficiency (Verma et al, 2015;Mohanty et al, 2017) and availability of micro nutrients (Nawalgatti et al, 2009;Shubhashree et al, 2011). Higher yield of treatment comprising of inorganic fertilizers in combination with organic manures may be due to the increased availability and uptake of macro and micro nutrients by the plant, resulting in higher rate of physiological (Barcchiya and Kushwah, 2017) and anabolic processes (Sen et al, 2006;Ramana et al, 2010). Sharma et al, 2018 reported increased uptake of N, P and K by French bean significantly through the combined application of vermicompost and N over the use of farmyard manure and nitrogen application.…”
Section: Resultsmentioning
confidence: 99%
“…inorganic source and control. Higher yield in treatment comprising inorganic fertilizers in combination with organic manures might be due to the increased availability and uptake of macro and micro nutrients by the plant, resulting in higher rate of physiological (Barcchiya and Kushwah, 2017) and anabolic processes (Ramana et al, 2010).…”
Section: Nutrient Uptakementioning
confidence: 99%